1984
DOI: 10.1073/pnas.81.6.1902
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin and cholecystokinin in pituitary neurons.

Abstract: Gastrins occur in the hypothalamo-hypophyseal neurons of all mammalian species examined. In addition, human, bovine, and murine hypothalamo-hypophyseal neurons contain the homologous cholecystokinins (CCKs). CCK also occurs in neurons innervating bovine melanotrophs. Al-though the concentration of gastrin is'of the same magnitude (15-30 pmol/g) in al neural lobes, the concentration of CCK varies from undetectable in pig and cat to 1 nmol/g in the cow. The constant occurrence of neurohypophyseal gastrin suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 20 publications
1
44
0
Order By: Relevance
“…In the latter tissues, L-364,718 is a very potent antagonist of CCK, and the sulfated form of CCK-8 is the preferred ligand. CCK-8 is the predominant form of CCK found in the rat neurohypophysis (16), but we have shown that the five C-terminal amino acids of CCK (Table 1) are sufficient to produce a potent secretion of the neurohypophysial hormones OT and VP.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter tissues, L-364,718 is a very potent antagonist of CCK, and the sulfated form of CCK-8 is the preferred ligand. CCK-8 is the predominant form of CCK found in the rat neurohypophysis (16), but we have shown that the five C-terminal amino acids of CCK (Table 1) are sufficient to produce a potent secretion of the neurohypophysial hormones OT and VP.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal tetrapeptide of gastrin has all the biological actions of the whole molecule and is shared by cholecystokinin (CCK) (Gregory, 1974). More recently the biologically active C-terminal octapeptide of CCK (CCK8) has been found in high concentrations in brain and peripheral neurones (Rehfeld et al, 1979). Apart from its presence in myenteric nerves and in some nerves to the urogenital tract (Rehfeld, 1980), neural CCK8 has not been found in the kidney.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies on pituitary CCK neurons (12), CCK was also found in the human adenohypophysis. Characterization of adenohypophyseal CCK with the radioimmunoassay library (6,11) has revealed a processing pattern that suggests a role for posttranslational modifications in the differentiation of endocrine cells.…”
mentioning
confidence: 99%